2022
DOI: 10.13057/biodiv/d230137
|View full text |Cite
|
Sign up to set email alerts
|

Traditional medicinal plants and their utilization by local communities around Lambung Mangkurat Education Forests, South Kalimantan, Indonesia

Abstract: Abstract. Nugroho Y, Soendjoto MA, Suyanto, Matatula J, Alam S, Wirabuana PYAP. 2021. Traditional medicinal plants and their utilization by local communities around Lambung Mangkurat Education Forests, South Kalimantan, Indonesia. Biodiversitas 23: 306-314. Lambung Mangkurat Education Forests (LMEF) is a unique forest area with high plant diversity, including medicinal plants. This study aimed to document the list of natural medicinal plant species in LMEF and analyze the community perceptions on utilizing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 29 publications
2
9
0
3
Order By: Relevance
“…Based on the deductions from previous research, several problems were identified that could threaten local wisdom in the Dayak community, including the Dayak Tamambaloh Tribe, including: (i) not having written documentation (Supiandi et al 2019a,b;Hussain et al 2022;Tahir et al 2021), (ii) delivered orally from generation to generation (Fatima et al 2019;Supiandi et al 2019a,b;Lulekal et al 2013;Nugroho et al 2022), (iii) influenced by technological advances and foreign cultures (Kustiawan 2007), (iv) land clearing for the development of industrial forests, oil palm plantations, illegal logging, shifting fields to threaten the sustainability of germplasm, as well as existing rare and endemic species (Setyawan 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the deductions from previous research, several problems were identified that could threaten local wisdom in the Dayak community, including the Dayak Tamambaloh Tribe, including: (i) not having written documentation (Supiandi et al 2019a,b;Hussain et al 2022;Tahir et al 2021), (ii) delivered orally from generation to generation (Fatima et al 2019;Supiandi et al 2019a,b;Lulekal et al 2013;Nugroho et al 2022), (iii) influenced by technological advances and foreign cultures (Kustiawan 2007), (iv) land clearing for the development of industrial forests, oil palm plantations, illegal logging, shifting fields to threaten the sustainability of germplasm, as well as existing rare and endemic species (Setyawan 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Results of empirical studies have shown that P. foetida, Caesalpinia sp, and D. cenniformis extracts are employed as traditional cough medicine. In contrast, the Aglaia species extract has therapeutic uses for treating chickenpox and herpes, and the Tetrastigma species extract is a traditional remedy for hemorrhoids [3,4]. In fact, these curative benefits of P. foetida, D. cenniformis, Caesalpinia species, Aglaia species, Tetrastigma sp, and L. indica seen above could be associated with their extracts containing various phytochemical compounds comprising flavonoids, alkaloids, and steroids.…”
Section: Introductionmentioning
confidence: 99%
“…2 They also have lower side effects compared to synthetic drugs. 3,4 Herbal therapy is popular in the community because it is considered an economical treatment that is easy to obtain and has minimal adverse effects. Medicinal herbs are not only obtained from wild plants, they are also widely cultivated.…”
Section: Introductionmentioning
confidence: 99%